An analysis of current mobile services and enabling technologies. (18th November 2005) - Jorstad, Ivar; Dustdar, Schahram; Do, Thanh Van
This paper presents the major technology enablers for mobile services in a comprehensive way and in relation to each other. Mobile services are subject to requirements not only from end-users and mobile network operators but also from wireless application service providers, the content providers, and equipment manufacturers. Each technology enabler is usually aiming at only a subset of the requirements and can be incomplete, inconsistent and overlapping with other technology enablers.